2019
DOI: 10.1101/519736
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical determination of absolute membrane potential

Abstract: 8All cells maintain ionic gradients across their plasma membranes, producing 9 transmembrane potentials (Vmem). Mounting evidence suggests a relationship between resting 10 Vmem and the physiology of non-excitable cells with implications in diverse areas, including 11 cancer, cellular differentiation, and body patterning. A lack of non-invasive methods to record 12 absolute Vmem limits our understanding of this fundamental signal. To address this need, we 13 developed a fluorescence lifetime-based approach (VF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…18 We also recently showed that the fluorescence lifetime of VF dyes varies with membrane potential, providing additional support for a PeT-based mechanism of sensing. 19 New indicators like VF2.1(OMe).H, with a sensitivity of 48% ΔF/F and improved cellular brightness compared to the chloro-substituted analog, allowed investigation of functional coupling across multiple neurons imaged simultaneously in intact, ex vivo leech preparations, 17 linking the topology of neuronal circuits to activity. 20 Subsequent studies coupled the use of improved VF dye VF2.1(OMe).H to innovative double-sided microscopies for comprehensive neuronal profiling across large numbers of neurons in intact leech ganglia.…”
Section: Green Dyes Including Vf Dyes Bodipy-vfs Fluorenevfs and Dsvfsmentioning
confidence: 99%
“…18 We also recently showed that the fluorescence lifetime of VF dyes varies with membrane potential, providing additional support for a PeT-based mechanism of sensing. 19 New indicators like VF2.1(OMe).H, with a sensitivity of 48% ΔF/F and improved cellular brightness compared to the chloro-substituted analog, allowed investigation of functional coupling across multiple neurons imaged simultaneously in intact, ex vivo leech preparations, 17 linking the topology of neuronal circuits to activity. 20 Subsequent studies coupled the use of improved VF dye VF2.1(OMe).H to innovative double-sided microscopies for comprehensive neuronal profiling across large numbers of neurons in intact leech ganglia.…”
Section: Green Dyes Including Vf Dyes Bodipy-vfs Fluorenevfs and Dsvfsmentioning
confidence: 99%
“…Inspired by a theoretical description of electron transfer for imaging voltage, 1 we have been developing molecular wire-based fluorescent voltage indicators, which we hypothesize use photo-induced electron transfer (PeT) 2 as a voltage-sensing trigger. These voltage-sensitive fluorophores, or VoltageFluors, respond to changes in membrane potential with submicrosecond response kinetics, [3][4][5] provide large, turn-on fluorescence responses to action potentials in neurons, and can operate with excitation wavelengths ranging from blue (VoltageFluor) [6][7] to green (Rhodamine Voltage Reporters, RhoVR) [8][9] and into the far red (Berkeley Red Sensor of Transmembrane potential, BeRST) 10 and infrared region with two photon excitation (2P). 9,[11][12] For voltage imaging with cellular resolution in vivo, molecular wire-based VoltageFluors possess the required speed, sensitivity, minimal invasiveness, and compatibility with 2P excitation.…”
Section: Introductionmentioning
confidence: 99%